Pengaruh Tekanan Finansial, Budaya Organisasi, Dan Pengendalian Internal Terhadap Kecenderungan Kecurangan - Anak Agung Ayu Eva Yanti; Ni Ketut Muliati; Ni Putu Yeni Yuliantari (Hita Akuntansi dan Keuangan, 2023)
Fraud is any form of deceptive activity that is done intentionally to harm another party and benefit the fraudster. Persistent fraud impedes an organization's progress and leads to bankruptcy. The purpose of this study is to determine the impact of financial pressures, organizational culture, and internal controls on Village Credit Institution's fraud tendencies. The survey was conducted in 13 village credit institutions in Melaya District. The sample size for this survey was 89 people. The sampling method used was saturated samples and was tested using multiple linear regression analysis techniques. The results of this study show that financial pressure has a significant positive impact on fraud propensity. Organizational culture has a negative and significant impact on fraud propensity. Internal controls have a significant negative impact on fraud trends.